Problem Based Learning Model Based on Field Trips on Learning Outcomes in Science Learning - Ni Kadek Dian Cahyani; I Gusti Ayu Tri Agustiana; Rendy Setyowahyudi (MIMBAR PGSD Undiksha, 2026)
Science and Natural Sciences (IPAS) learning still faces challenges, particularly low student learning outcomes caused by the suboptimal implementation of problem-based learning and the dominance of conventional, teacher-centered approaches. This study aims to examine the effect of a field trip-based Problem Based Learning model on students’ learning outcomes. This research employed a quasi-experimental design with a non-equivalent post-test only control group design. The subjects of the study involved fifth-grade elementary school students divided into experimental and control groups. Data were collected using an objective test to measure students’ learning outcomes. The data were analyzed using descriptive and inferential statistics through an independent sample t-test. The results showed that the t-value was higher than the t-table value at a 5% significance level, indicating a significant effect of the field trip-based Problem Based Learning model on students’ learning outcomes. These findings suggest that integrating problem-based learning with direct learning experiences outside the classroom enhances students’ conceptual understanding in a more meaningful way. The implication of this study is that this learning model can serve as an alternative innovative instructional strategy to improve learning outcomes and promote active student engagement in the learning process.